The Comparison of Brachial Artery Parameters between the Clinical Cuff, Pneumatic Controlled Air Band (KAATSU), and Elastic Band during Blood Flow Restriction at the same Perceived Tightness - Gaspar, Alexandra Passos; LDNJ, De Matos; S, Amorim; RS, De Oliveira; RV, Fernandes; G, Laurentino (Journal of Sports Medicine and Therapy, 2024)
The Blood Flow Restriction (BFR) technique is based on cuffs connected to a pressure device that induces partial arterial inflow. BFR combined with exercise has already been proven to increase strength, muscle mass, and muscular endurance. However, some BFR devices with pneumatic air bands, such as KAATSU (KA), are expensive and less accessible, making either a Sphygmomanometer Cuff (SC) or Elastic Band (EB) an interesting alternative. However, vascular parameters in response to blood flow restriction during KA, EB, and SC have not yet been compared. Purpose: The aim of this study was to compare the brachial blood flow behavior during restriction using bands such as KA, SC, and EB on the same perceived tightness. Methods: Thirty healthy men participated in a prospective crossover study. Participants underwent blood flow measurements before and during KA, SC, and EB use, with KA-perceived tightness taken as a reference. The brachial blood flow volume, the diameter of the artery, and blood flow velocity were measured before and immediately after the cuff’s inflation at a specific tightness. Results: Blood flow volume was significantly reduced in KA (52%, ES: 1.38), SC (61.7%, ES: 1.29), and EB (41.5%, ES: 1.22) (p <.0001). In addition, blood flow velocity was significantly reduced in KA (12.9%, ES: 0.74), SC (23.8%, ES: 1.02), and EB (25.6%, ES: 1.02) (p <.0001). No significant changes were observed in the diameter of the brachial artery for any condition (p > 0.05). Conclusion: Brachial blood flow behavior was similar between pneumatic controlled air band (KA), SC, and EB cuffs at the same perceived tightness. Highlights Growing evidence suggests that blood flow restriction is an interesting technique to improve muscle mass and strength with less articular impact and practical applications are yet to be explored. Different bands and devices have been used to apply in patients the technique and but, methods are still too heterogenous to be compared in the expected results. Although studies in the BFR literature have shown that blood flow restriction is applied according to Arterial Occlusion Pressure (AOP) and the devices and techniques are trying to standardize it, there is still a lack of information on this matter. More studies are needed to evaluate their similarity and also understand their safety